Perkembangan Dan Dinamika Pasar Sukuk Domestik: Sebuah Kajian Agenda Dan Kebijakan - Ayief Fathurrahman (Universitas Islam Lamongan, 2017)
One of Islamic financial sectors that attract much interest from the business community around the world is the global sharia obligation (sukuk) market. Sukuk has become an important instrument in sharia financial system, both as a financing instrument and investment. This instrument grew rapidly along with the growth and development of other conventional financial instruments. This estimation is based on the large number of infrastructure projects from the Gulf region and across the Muslim world seeking capital for development. This paper tries to answer the question: What are the factors that led to the issuance and development of sukuk in three countries, namely Indonesia, Malaysia, and Turkey? The result shows that government policy and agenda in order to develop sukuk can be concluded that the issuance of sukuk from three countries Indonesia, Malaysia and Turkey is influenced by several factors. However, the most dominant factor, even the factor that has always been the cause of the increased issuance of sukuk in three countries is the regulatory or policy factor, especially regarding the tax on sukuk and the existence of strong legal infrastructure as an umbrella of sukuk practice in a country. It can be said that the smaller the tax on the issuance of sukuk the more sukuk will be published. Then the second element of the regulatory factor is the existence of security guarantees in its implementation from the side of positive law imposed in a State. This factor is also very important especially in cases in Indonesia. With the legal clarity, there is no slit in the weakness of sukuk when compared with bonds. It is different from the two countries above, the advancement of sukuk issuance apart from being influenced by regulatory factors, Malaysia seems to be more benefited by the perception of the global community that Malaysia has become the Islamic economic and finance center in the world, so Malaysia is considered more experienced in this sector. This is a factor that may be considered by global investors, so that Malaysia is to be the right destination for sharia-based investment. Keywords: Sukuk Development, Indonesia, Malaysia, Turkey